Proyecto de expansión de la empresa Abba Amiros Tubos de cartón - Camino Hidalgo, Angela Marcela (2006)
The expansion of the company will be to reorganize their functional organizational structure, redeploy, financial, machinery and equipment as well as the application of the sales channels both nationally human resources to increase our working capital and reduce costs manufacturing.